Bacillus subtilis KLBMPGC81 suppresses appressorium-mediated plant infection by altering the cell wall integrity signaling pathway and multiple cell biological processes in Magnaporthe oryzae - Li, Lianwei; Li, Yanru; Lu, Kailun; Chen, Rangrang; Jiang, Jihong (Frontiers in Cellular and Infection Microbiology, 2022)
Magnaporthe oryzae is one of the most destructive crop pathogens in the world, causing huge losses in rice harvest every year. Bacillus subtilis is a potential biocontrol agent that has been explored in many crop systems because it is a potent producer of bioactive compounds. However, the mechanisms by which these agents control rice blasts are not fully understood. Here, we showed that B. subtilis KLBMPGC81 (KC81) and its supernatant (SUP) have high antimicrobial activity against M. oryzae strain Guy11. To better exploit KC81 as a biocontrol agent, the mechanism by which KC81 suppresses rice blast pathogens was investigated. This study shows that KC81 SUP is effective in controlling rice blast disease. The SUP has a significant effect on suppressing the growth of M. oryzae and appressorium-mediated plant infection. KC81 SUP compromises cell wall integrity, microtubules and actin cytoskeleton, mitosis, and autophagy, all of which are required for M. oryzae growth, appressorium development, and host infection. We further show that the SUP reduces the activity of the cyclin-dependent kinase Cdc2 by enhancing the phosphorylation of Cdc2 Tyr 15, thereby impairing mitosis in M. oryzae cells. SUP induces the cell wall sensor MoWsc1 to activate the cell wall integrity pathway and Mps1 and Pmk1 mitogen-activated protein kinases. Taken together, our findings reveal that KC81 is an effective fungicide that suppresses M. oryzae growth, appressorium formation, and host infection by abnormally activating the cell wall integrity pathway, disrupting the cytoskeleton, mitosis, and autophagy.